The Effects of Motivation, Creativity and Social Media Usage for Information Seeking on Product Innovation - Rizka Putri Pranandari; Atsushi Aoyama (CV. Ulil Albab Corp, 2024)
Micro, Small, and Medium Enterprises (MSME) have important role to the national economy in Indonesia. In this regard, innovation is crucial because it is one of the major keys to develop the competitiveness of the MSME. Some previous studies indicate that there are various factors that influence innovation in the business organization. In this study, we try to investigate the effect of intrinsic motivation, creativity as well as social media usage for information seeking on product innovation among culinary MSME. We gathered 102 responses from the owner or managing staff of a culinary MSME through paper-based surveys. We delimit the location of the surveys, which is only in the area around the campuses in Depok district, Sleman, Yogyakarta because we argue that the MSMEs located in such area tend to be more innovative since their market niche are college students who are coming from the younger generation. The results of the hypothesis tests using PLS-SEM approach indicate that intrinsic motivation and creativity have positive and significant effect on product innovation. The same goes with social media usage for information seeking. Some implications are discussed in the later part of this article.